On topological characterization of some properties of measures using Ocan typetopologies - Praninskas, Gintaras (Lietuvos matematikos rinkinys, 2010)
In the article is given topological characterization of prolongement of measure from algebra A subsetsto σ-algebra subsets σ(A) as prolongement of measure as continuos function from spaceof subsets A to space σ(A) in some Ocan type topology. The topological of Radon and regularity of measurecharacterization using Ocan type topologies also is given.O топологической характеристике некоторых свойств мер посредством очановских топологийВ статье дается топологическая характеристика продолжения меры, так же топологическая характеристика радоновости и регулярности мер на σ-алгебре Борелевских множеств топологического пространства посредством экспоненциальных топологий типа Очана.
Keywords: topological space; σ-algebra; space of subsets; prolongement of measure; Radon and regular measures; Ocan type topologies on space of subsets